Do momento da exigibilidade das astreintes - Souza, Veridiana Silva Teodoro de (2013)
The object of this study is the analysis of the fee estabilished by the article 461 of the Brazilian Civil Procedure Code, focusing specially on the rigth moment of its applicability. For that matter, it is necessary to reflect towards the concept, purpose and legal nature of the fine and the possibility of classifying it as enforceable title. Having as a starting point the set premises about the theme, the project identifies three currents on the exact moment of chargeability i) provisional enforceament before double jeopardy ii) final execution before double jeopardy iii) execution after double jeopardy. Thenceforward, deepening on the meanings of the pleas from each of the identified positions, it is presented a conclusion considering that the enforceable titles execution must begin from double jeopardy or on a provisional basis, whenever there is a penalty as appeal without suspensory effect